Human Papillomavirus In Pregnancy - Pardo, Luis Marín Arias; Arreaga, Gabriela Belén Espinosa; Cabrera, Martha Beatriz Baquerizo; Peralta, Sonia Kattya Robles; Navas, Welky Giuseppe Colamarco; Calle, Pamela Monserrath Quito (Migration Letters, 2024)
Infections by the human papillomavirus (HPV) have currently increased, becoming a common infection with a significant rise in the population, with pregnant women being the most affected group, posing risks to both the mother and the newborn. HPV during pregnancy can lead to a variety of complications, ranging from mild to severe, representing a risk for both the mother and the fetus. These complications in the mother are attributed to the numerous physiological changes experienced during pregnancy, which can favor the development of pathological alterations. The present research aimed to analyze and synthesize the available scientific evidence to understand how HPV infection can affect pregnancy. The methodology involved a systematic review, where scientific articles from reliable databases were selected. The results revealed that during pregnancy, especially in the first two trimesters, there is a decrease in immunity or immunosuppression, which can increase susceptibility to HPV infection or viral replication. There is a possibility of vertical transmission of HPV from mother to newborn during childbirth, resulting in the appearance of anogenital and laryngeal lesions in the newborn. In conclusion, the accurate diagnosis of HPV infection during pregnancy is essential to manage complications adequately and apply safe treatments, considering the limitation of certain therapeutic approaches during gestation.